Hobbes: la relación entre razón, pasión, técnica y ciencia civil (2016)
That which is technical must be subordinate to that which is political or otherwise it converts itself into an autonomous instance that alienates man from his essence, his political being, leading to the dehumanisation of man. The emergence of the relationship between technique and politics goes back to the beginning of modern political thought, particularly the civil science postulated by Hobbes. In this essay, the author will present this relationship in three stages. In the first two, the conception of the individual as a being that is cognoscente and passionate is demonstrated. In the third stage the author will present the relationship proposed by Hobbes between science, man, technique and politics.